2022
DOI: 10.1097/mca.0000000000001119
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of sudden cardiac arrest in the immediate post-percutaneous coronary intervention period for ST-elevation myocardial infarction: a single-center study

Abstract: Background Data on the incidence, predictors, and outcomes of sudden cardiac arrest (SCA) in the immediate post-percutaneous coronary intervention (PCI) period for ST-elevation myocardial infarction (STEMI) are limited. ObjectivesThe study aimed to investigate the trends and predictors of SCA occurring within 48 h post PCI for STEMI. MethodsWe systematically reviewed data from the electronic medical records of 403 patients who underwent PCI for STEMI between January 2014 and December 2019. Trends in the incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A smaller single-center study found that IHCA within the first 48 hours after PCI for STEMI occurred in 11% (44) of 403 patients reviewed. 85…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…A smaller single-center study found that IHCA within the first 48 hours after PCI for STEMI occurred in 11% (44) of 403 patients reviewed. 85…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…Over the past decade, there has been a decrease in STEMI‐related mortality in the United States and globally. 44 , 45 , 46 , 47 In another study investigating the national trends in STEMI outcomes, in‐hospital rate mortality decreased from 12.4% in 2002 to 10.5% in 2016, with an annual percentage change of −0.85%, (95% CI, −1.24 to −0.45; P <0.001). 46 Interestingly, in our study, from 2008 to 2019, the adjusted odds ratio for in‐hospital mortality remained unchanged in women and men aged 18 to 55 years.…”
Section: Discussionmentioning
confidence: 99%